The relationship between teacher support and positive emotions in Chinese higher vocational students: multiple mediating effects of procrastination behavior and interpersonal assistance - Wang, Junhui; Zhou, Cheng; Song, Qiming; Xu, Fuxiao (Frontiers in Psychology, 2023)
Background: In China, more than 5 million students enter higher vocational colleges each year, and the positive emotions of their students merits much attention. Purpose: This study aimed to explore the effect of teacher support on positive emotions among higher vocational students by further investigating the mediating role of procrastination behavior and interpersonal assistance. Methods: A questionnaire survey was conducted with 676 higher vocational students from Zhejiang Province, China. We used SPSS 26.0 for data analysis, which included correlation analysis, regression analysis and bootstrap-mediated effects tests. Results: Teacher support positively predicted positive emotions (β=0.302, P<0.001) and interpersonal assistance (β=0.170, P<0.001), while procrastination behavior negatively predicted interpersonal assistance (β=-0.161, P<0.001) and positive emotions (β=-0.088, P<0.01). Interpersonal assistance positively predicted positive emotions (β=0.279, p<0.001). This study found that teacher support positively predicted positive emotions; either procrastination behavior or interpersonal assistance independently mediated the relationship between teacher support and positive emotions. These two variables (procrastination and interpersonal assistance) also acted as a chain mediator between teacher support and positive emotions. The direct effect of teacher support and the mediating role of interpersonal assistance had a greater effect. Conclusion: The study deeply explored the effects of teacher support on positive emotions among Chinese higher vocational students and found that teacher support plays an important role in positive emotion management. At the same time, we found the key roles played by procrastination behavior and interpersonal assistance between teacher support and positive emotion, which could provide data support and decision-making reference for enhancing higher education students’ well-being and positive emotions. This study can be regarded as a case study of social support theory and demonstrates the applicability of the theory in the field of positive emotions of higher vocational students.